Germination of forage species in the presence of cadmium, copper and lead - Rosniecek, Kathleen Steiner; Campos, Mari Lucia; Coelho, Cileide Maria Medeiros; Miquelluti, David José; Schutz, Emili Louise Diconcili (Revista de Ciências Agroveterinárias, 2020)
Soil contaminated with trace elements needs to introduce tolerant species and rapid growth. The objective of this study was to evaluate the germination of forage species Brachiaria humidicola cv. Tupi, Panicum maximum cultivars Aruana and Tanzania in the presence of trace elements cadmium (Cd), copper (Cu) and lead (Pb). The experiment was conducted in the Laboratory for Seed Analysis (CAV-UDESC), the tests were conducted in the absence of the elements (control - 0 mg L-1), and in the concentrations of 3, 180 and 200 mg L-1 for Cd, Pb and Cu respectively. Germination percentage (G), Germination Speed ​​Index (GSI), Vigor (V) and tolerance index for aerial parts (AP) and root (R) were calculated. The presence of Cu inhibited the germination, root emission and aerial part of the species P. maximum cv. Aruana, as for vigor index was affected by the presence of Cu for the species P. maximum cv. Tanzânia and B. humidicola cv. Tupi. The percentage of germination, germination speed index and shoot length of the three species studied were affected by the presence of Cd. The presence of Pb affected shoot length and root length, and vigor index for P. maximum cv. Aruana and P. maximum cv. Tanzânia. The decreasing order of species sensitivity in the presence of Cd and Pb was P. maximum cv. Aruana > P. maximum cv. Tanzânia > B. humidicola cv. Tupi.